Canthin-6-one alkaloids from Brucea mollis var. Tonkinensis - Ouyang, Yishan; Koike, Kazuo; Ohmoto, Taichi (Phytochemistry, 1994)
Three new alkaloids were isolated from the root-wood of Brucea mollis var. tonkinensis collected in China. Their structures were determined to be 11- O-β- d-glucopyranosyl-(1 → 6)-β- d-glucopyranosylcanthin-6-one, 5- O-β- d-glucopyranosyl-(1 → 6)-β- d-glucopyranosylcanthin-6-one and 11-hydroxycanthin-6-one- N-oxide, by chemical and spectral methods. In addition, two known alkaloids, canthin-6-one and canthin-6-one- N-oxide, were isolated.